Virtuoso of Pathophysiological Experiment: to the 100th Anniversary of Academician V. K. Kulagin - V. N. Tsygan; S. A. Mamaeva (Общая реаниматология)
Aim. To analyze the contribution of V. K. Kulagin, Doctor of Medical Sciences, Professor of the Department of Pathological Physiology of the Military Medical Academy into development of scientific perspectives concerning the etiology, pathogenesis and therapy of traumatic shock, following thorough analysis of 1950–1980s series of featured publications. We analyzed the general theoretical views of the scientist, his methodological preferences in organizing laboratory experiments, the methodology for developing standard models for conducting experiments, choosing indicators and evaluation criteria. We brought to recollection the proposed by V. K. Kulagin approach to traumatic shock staging and phases relative to the leading pathogenetic factor; highlighted some of the key topics and results of his experimental research related to individual resistance to shock, prerequisites of shock irreversibility and factors complicating the course of traumatic shock.Conclusion. Theoretical and experimental inventions of V. K. Kulagin are relevant to the present day and are of great importance for further progress of medical science.